Exercise intensity and metabolic response in singles tennis - Christmass, M.; Richmond, S. E.; Cable, N. T.; Arthur, P. G.; Hartmann, P. E. (Journal of Sports Sciences, 1998)
The aim of this study was to determine exercise intensity and metabolic response during singles tennis play. Techniques for assessment of exercise intensity were studied on-court and in the laboratory.We conclude that changes in exercise intensity based on measurements of heart rate and a time–motion analysis of court movement patterns explain the variation in lactate concentration observed during singles tennis, and that measuring heart rate during play, in association with preliminary fitness tests to estimate VO2, will overestimate the aerobic response.